Unveiling New States in 98Zr: Insights from β-decay and γ-γ Angular-Correlation Studies - Mashtakov K. R.; Garrett P. E.; Olaizola B.; Andreoiu C.; Ball G. C.; Bender P.; Bildstein V.; Chester A.; Cross D. S.; Dawkins H.; Demand G. A.; Diaz-Varela A.; et al. (EPJ Web of Conferences)
The nuclear structure of the 98Zr nucleus was studied through the β− decay of 98 Yg.s. at the TRIUMF-ISAC facility. The use of the 8π γ-ray spectrometer with its ancillary detectors SCEPTAR and PACES enabled γ-γ and γ-e− coincidence measurements as well as γ-γ angular correlations. The level spin assignments and transition mixing ratios obtained in this study were in good agreement with previous results. Furthermore, 12 previously unknown states in the low-energy region of 98Zr were identified, including the 0+5 and 0+6 levels at 2418 and 2749 keV, respectively. The 2+ and I = 1 natures for multiple newly observed and previously known (but not firmly assigned) states have been established. Additionally, the previously assumed pure E2 character of the 2+2 → 2+1 367.8-keV transition was confirmed.